Key Areas that Support Economic Growth (International Journal of Humanities and Social Sciences Reviews, 2024)
Economic growth is a vital aspect of a country's development, and achieving it requires contributions from various key fields. This research discusses and identifies key areas that significantly support economic growth. Modern technology is the main catalyst in the era of globalization, accelerating productivity, efficiency and innovation. Education is recognized as the foundation of human resource development, playing a key role in improving the quality of the workforce and creating an environment that supports innovation. This research also highlights the interconnections between key sectors, showing that sustainable economic growth requires effective synergies between them. In addition, external factors such as government policy, political stability, and international market accessibility also influence economic growth.